Transgenerational transmission in psychoanalysis: A phenomenology of dislocating errands - Apprey, Maurice (The Indo-Pacific journal of phenomenology, 2023)
In the process of psychical transmission from one generation to the next, who asks what of whom? The evocative expression of an ‘errand’ suggests that a subject is sent on a mission, sent in error, wanders away, and returns home, adversely changed. A vocative imperative is at the heart of a mission. When there is a call from an anterior Other, there must be a response. Before, there was an experience of a call and its response, then, there would be an errand. Precisely, the subject is preceded by the self-same subject’s constituted and appropriated mandate from an anterior object. To upend an aberrant errand, a subject must reconfigure a posted imperative, ever altering, again and again, the call and summons of an alien and unwelcome guest turned host. Otherwise, the dissonant and unwelcome guest turned host may transform the naïve subject into a ghost, a revenant that disappears and returns to haunt the subject. Thanks to the new and public space in the clinical setting, the entity that listens to the sub-ject will come to know that reception and perception of an errand is communalised in ways where there is a constant alteration, revision and co-creation of meanings of the received and perceived phenomenon through reciprocal connection and reciprocal correction. When subject’s experiential acquisitions enter that clinical setting, a resolute upending of a retrogressive descent toward death may occur. Hence, the meaning of staying alive for an Other who is otherwise dislocated, thrown, posted into a transgenerational spiral, toward death. A toxic errand is thus potentially aborted in that new space where a new relationship for resubjectivising and sublimating the unwanted mandate happens. Resubjectivising the injected errand becomes the exit strategy so that positive change is now conceivable.